2012
DOI: 10.1186/1475-2840-11-137
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the FTO rs9939609 and the MC4R rs17782313 polymorphisms with type 2 diabetes are modulated by diet, being higher when adherence to the Mediterranean diet pattern is low

Abstract: BackgroundAlthough the Fat Mass and Obesity (FTO) and Melanocortin-4 Receptor (MC4R) genes have been consistently associated with obesity risk, the association between the obesity-risk alleles with type 2 diabetes is still controversial. In some recent meta-analyses in which significant results have been reported, the associations disappeared after adjustment for body mass index (BMI). However gene-diet interactions with dietary patterns have not been investigated. Our main aim was to analyze whether these ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 60 publications
6
96
1
3
Order By: Relevance
“…For example, Moore and co-workers 48 showed that the significant association between ENPP1 and increased incidence of T2DM was mediated by lifestyle or metformin intervention. Ortega-Azorin and co-workers 49 also found an interaction between FTO and mediterranean diet in determining T2DM, with carriers of the FTO-rs9939609 minor allele on a low Meddiet having a higher risk of prevalent T2DM than individuals homozygous for the major allele. In a European-American population group, Mattei and co-workers 50 observed a significant interaction between the TCF7L2-rs12255372-TT risk genotype and fat intake for changes in BMI, total fat mass, and trunk fat mass at 6 month of lifestyle intervention.…”
Section: Limitationsmentioning
confidence: 89%
“…For example, Moore and co-workers 48 showed that the significant association between ENPP1 and increased incidence of T2DM was mediated by lifestyle or metformin intervention. Ortega-Azorin and co-workers 49 also found an interaction between FTO and mediterranean diet in determining T2DM, with carriers of the FTO-rs9939609 minor allele on a low Meddiet having a higher risk of prevalent T2DM than individuals homozygous for the major allele. In a European-American population group, Mattei and co-workers 50 observed a significant interaction between the TCF7L2-rs12255372-TT risk genotype and fat intake for changes in BMI, total fat mass, and trunk fat mass at 6 month of lifestyle intervention.…”
Section: Limitationsmentioning
confidence: 89%
“…Ortega-Azorín et al (2012) found a significant gene-diet interaction of the FTO rs9939609 and MC4R rs17782313 polymorphisms with type 2 diabetes depending on diet, in which the Mediterranean diet counteracts the genetic predisposition. A cross-sectional study found that individuals carrying both AA risk allele of the rs9939609 polymorphism were positively associated with a high intake of total fat (>34% energy) and low fiber consumption (<16 g/day), independently of BMI (Steemburgo et al 2013).…”
Section: Preventionmentioning
confidence: 92%
“…The Fat Mass and Obesity (FTO) gene is considered as leading obesity and type 2 diabetes [8]. The FTO rs9939609 minor allele, the risk allele for obesity, increased the risk of type 2 diabetes, this association remaining statistically significant even after adjustment for BMI [9].…”
Section: Discussionmentioning
confidence: 99%